Globalization and the impact on Singapore's industrial structure. - Loke, Lilian Phaik Yeen. (2010)
Since the 1980s, Singapore's industrial structure has been evolving, from being labour-intensive to becoming more capital-intensive. Now, Singapore has become a high-income country and is highly ranked in the world in terms of competitiveness. In this paper, we study whether globalization played a role in shaping Singapore's industry structure from 1980s onwards. Specifically, we test whether Foreign Direct Investment (FDI) and Trade impacts Singapore's capital-labour ratio and causes changes to Singapore's labour structure. From our analysis, our results suggest that both FDI and Trade affects Singapore's capital-labour ratio, particularly for FDI. We also found evidence which suggests that globalization causes changes in Singapore‘s labour structure, thus affecting the skill intensity in Singapore's workforce. In order to maintain its competitiveness, Singapore has to move towards more innovation and value creation along with upholding the political stability within the country and ensuring strong relationships with its neighboring countries.